2009
DOI: 10.1262/jrd.09-089a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Noninvasive Monitoring System for Evaluation of Oct-3/4 Promoter Status in Miniature Pig Somatic Cell Nuclear Transfer Embryos

Abstract: Abstract. The present study was carried out to develop a noninvasive monitoring system for evaluation of Oct-3/4 promoter gene status in miniature pig somatic cell nuclear transfer (SCNT) embryos during in vitro development. Miniature pig fetal fibroblasts (MPFFs) were transfected with a gene construct consisting of two expression units, a mouse Oct-3/4 promoter-driven enhanced green fluorescent protein (EGFP) gene (EGFP expression only detected in Oct-3/4-expressing cells) and a neomycin resistance gene. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
3
11
0
1
Order By: Relevance
“…4C, lane 8) may be ascribed to failure to express their α-GalT mRNA at a level detectable by RT-PCR, as previously pointed out. This phenomenon may be related to the failure of proper reprogramming of donor nuclei after SCNT, since gene activation of embryonic and pluripotency-related genes is sometimes suppressed [43,44]. In our preliminary data, expression of α-GalT mRNA increased gradually with progression towards the blastocyst stage (unpublished results).…”
Section: Discussionmentioning
confidence: 65%
“…4C, lane 8) may be ascribed to failure to express their α-GalT mRNA at a level detectable by RT-PCR, as previously pointed out. This phenomenon may be related to the failure of proper reprogramming of donor nuclei after SCNT, since gene activation of embryonic and pluripotency-related genes is sometimes suppressed [43,44]. In our preliminary data, expression of α-GalT mRNA increased gradually with progression towards the blastocyst stage (unpublished results).…”
Section: Discussionmentioning
confidence: 65%
“…The resulting embryos exhibited EGFP expression at the morula to blastocyst stages. Immunohistochemical staining using anti-Oct-3/4 antibodies revealed that the EGFP expression pattern seen in these SCNT embryos was correlated with that of endogenous Oct-3/4 gene [16]. Therefore, this Oct-3/4-EGFP-based noninvasive monitoring system would be useful for evaluation of the reprogramming level of SCNT embryos in miniature pigs.…”
mentioning
confidence: 91%
“…In addition, the Oct-3/4 expression pattern in the tissues of adult pigs is the same as that in adult mice; Oct-3/4 is expressed in PGCs, the ovary and the testis, but not in the heart, liver, lung, kidney, spleen and fibroblasts [15]. Based on this background, Oct-3/4 appears to be a good marker for evaluating the reprogramming level of SCNT embryos.In the previous studies [16,17], we produced SCNT embryos by transferring miniature pig fetal fibroblasts (MPFFs) transfected with a plasmid (termed pOEIN) that contains a mouse Oct-3/4 promoter-driven enhanced green fluorescent protein (EGFP) cDNA into enucleated pig oocytes. The resulting embryos exhibited EGFP expression at the morula to blastocyst stages.…”
mentioning
confidence: 99%
See 2 more Smart Citations